Using Nonuniform Fiber to Generate Slow Light via SBS - Li, Wenhai; Bao, Xiaoyi; Kalosha, V. P.; Chen, Liang; Li, Ming-Jun (Research Letters in Optics, 2008)
The data pulse delay based on slow light induced by stimulated Brillouin scattering (SBS) in a nonuniform dispersion decreasing fiber (DDF) is demonstrated experimentally, and the distortions of data pulses at different beat frequencies are studied. We found that a delay exceeding a pulse width can be achieved at particular beat frequency, and the DDF has larger delay versus gain slope coefficient with much better output pulse quality than single-mode fiber.